Beyond paradigm: The 'what' and the 'how' of classroom research. (October 2014) - Whong, Melinda; Gil, Kook-Hee; Marsden, Heather
This article reviews studies in second language classroom research from a cross-theoretic perspective, arguing that the classroom holds the potential for bringing together researchers from opposing theoretical orientations. It shows how generative and general cognitive approaches share a view of language that implicates both implicit and explicit knowledge, and that holds a bias towards implicit knowledge. Arguing that it is implicit knowledge that should be the object of research, it proposes that classroom research would benefit from incorporating insights from a generative understanding of language. Specifically, there is a need for a more nuanced view of the complexity of language in terms of linguistic domain, and the interaction between those domains. Generative second language acquisition research that shows developmental differences in terms of both linguistic domain and interface is reviewed. The core argument is a call for more attention to the 'what' of language development in classroom research and, by implication, teaching practice. As such, the language classroom is seen to offer potential for research that goes beyond paradigm to address both the 'what' and the 'how' of language development.